1993
DOI: 10.1152/ajpheart.1993.264.4.h1124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticotropin-releasing factor on isolated rat heart activity

Abstract: We investigated effects of bolus administration of corticotropin-releasing factor (CRF) on parameters of cardiac activity in isolated working rat hearts. Effects at a dose of 5 micrograms of CRF were compared in hearts perfused with Krebs-Henseleit solution, norepinephrine (NE, 10(-9) M), propranolol (3 x 10(-6) M), NG-nitro-L-arginine (L-NNA, 3 x 10(-5) M), or indomethacin (3 x 10(-5) M). CRF increased coronary flow for > 30 min (P < 0.01) with maximum increases of 31.7%, suggesting a prolonged vasodilatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 0 publications
4
25
0
2
Order By: Relevance
“…Previous studies have demonstrated that coronary blood flow and aortic pressure changes during CRF perfusion of isolated rat hearts were not affected by cotreatment with propranolol (34). Our data support these findings in that pretreatment with the ␤-AR antagonist, esmalol, did not interfere with enhancement of peak (ϩ) dP͞dt by UcnII treatment of wild-type mice.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated that coronary blood flow and aortic pressure changes during CRF perfusion of isolated rat hearts were not affected by cotreatment with propranolol (34). Our data support these findings in that pretreatment with the ␤-AR antagonist, esmalol, did not interfere with enhancement of peak (ϩ) dP͞dt by UcnII treatment of wild-type mice.…”
Section: Discussionsupporting
confidence: 89%
“…There is clear agreement in the literature that CRF ligands cause mesenteric (Rohde et al, 1996;Barker and Corder, 1999) and coronary (Grunt et al, 1993;Terui et al, 2001;Huang et al, 2002) vasodilatation, but there is no consensus with regard to the mediators involved in those responses or the degree of their dependence on the endothelium. For example, Grunt et al (1993) provided evidence in the isolated rat heart to suggest that the coronary vasodilator action of CRF involved the endothelial release of NO and prostacyclin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Grunt et al (1993) provided evidence in the isolated rat heart to suggest that the coronary vasodilator action of CRF involved the endothelial release of NO and prostacyclin. In contrast, Terui et al (2001), using the same preparation but with UCN1 rather than CRF as the agonist showed an involvement of prostanoids but not NO.…”
Section: Discussionmentioning
confidence: 99%
“…3B) vascular system in contrast to its hypertensive effect, which it mediates through the hypothalamic-pituitary-adrenal axis and sympathetic autonomic nervous system (4,(9)(10)(11). Additionally, a direct positive inotropic effect of CRF has been shown on isolated guinea pig ventricular myocardium (28) and on isolated working rat heart (27,34). CRF also induces, in isolated rat heart, a short-term increase in the release of atrial natriuretic factor, perhaps supplying enough to modulate blood pressure through its diuretic, natriuretic, and vasodilatory actions (34).…”
Section: Resultsmentioning
confidence: 99%
“…This receptor is undetectable in other tissues examined, including heart and skeletal muscle (18)(19)(20). However, physiological studies have indicated the presence of a CRF-responsive receptor that mediates a positive inotropic effect in isolated heart (27) and myocardium (28) and suppression of vascular leakage in skeletal muscle (29). Here we report the identification and characterization of another receptor that mediates intracellular responses induced by sauvagine, urotensin I, and CRF.…”
mentioning
confidence: 99%